Advaned batteries : Materials science aspect - Robert, A. Huggins (Springer, 2010)
Storage and conversion are critical components of important energy-related technologies. Advanced Batteries: Materials Science Aspects employs materials science concepts and tools to describe the critical features that control the behavior of advanced electrochemical storage systems.